PENGETAHUAN MENGENAI ANTIBIOTIKA DI KALANGAN MAHASISWA ILMU ILMU KESEHATAN UNIVERSITAS GADJAH MADA YOGYAKARTA - Rizky Indah Pratiwi; Rustamadji Rustamadji; Aris Widayati (Sanata Dharma University, 2013)
Abstract: Inappropriate use of antibiotics, both prescribed and non-prescribed, is a globalpublic health problem. In Indonesia, there is an increase of self-medication with antibiotics in thecommunity in the last decade. Health practitioners are the main source of information and adviceon self-medication with antibiotics in the community. Therefore, it is important to investigateknowledge of antibiotics among students of health sciences because they are candidates forfuture health practitioners. This study is an observational cross-sectional survey using avalidated questionnaire. Respondents were 150 students of health sciences faculties at GadjahMada University Yogyakarta who were selected using a non-random convenience samplingtechnique. Of the 150 respondents, 79%(119) were familiar with antibiotics. Only these data (n=119) were subsequently analysed. Overall, they had appropriate knowledge about efficacy ofantibiotics for bacterial infections and risks of antibiotic use, i.e. allergic reactions and antibioticresistance. However, their knowledge about efficacy of antibiotics for viral infections and the useof antibiotics immediately for fever were not appropriate. In general, 34% of respondents hadhigh level of knowledge about antibiotics, 54% in the moderate level and 12% in the low level.Keywords: knowledge of antibiotics, health sciences students